Social media and the new struggles of young people against marginalisation: a challenge to missional ecclesiology in Southern Africa - Nel, Reggie (Stellenbosch Theological Journal, 2016)
Social media technologies have become a prominent feature of public life, but also the personal lives of young people. The question is whether the academic discourses on the missional church in southern Africa have taken this trend into consideration adequately. This article addresses this question by introducing a postcolonial missiological perspective on social media and the new struggles of young people against marginalisation. Through a literature review, the article appropriates research from sociologists, in particular Manuel Castells, firstly to show how subjects are constructed in this new, networked world order and secondly to show how social transformation is framed and engendered. It is concluded that these findings are the basis for the notion of the missional church as a social network. It is recommended that a subtheme, which prioritises the role of social media in this age of the network society, be established in the academic discourse on the southern African missional church in order to continue the dialogue with young people in their contemporary struggles.